Severity-adjusted evaluation of newborn screening on the metabolic disease course in individuals with cytosolic urea cycle disorders - Posset, Roland; Kölker, Stefan; Gleich, Florian; Okun, Jürgen G.; Gropman, Andrea L.; Nagamani, Sandesh C. S.; Scharre, Svenja; Probst, Joris; Walter, Magdalena; Hoffmann, Georg F.; Garbade, Sven; Zielonka, Matthias (Molecular genetics and metabolism, 2020)
Objective - The implementation of newborn screening (NBS) programs for citrullinemia type 1 (CTLN1) and argininosuccinic aciduria (ASA) is subject to controversial debate. The aim of this study was to assess the impact of NBS on the metabolic disease course and clinical outcome of affected individuals. - Methods - In 115 individuals with CTLN1 and ASA, we compared the severity of the initial hyperammonemic episode (HAE) and the frequency of (subsequent) HAEs with the mode of diagnosis. Based on a recently established functional disease prediction model, individuals were stratified according to their predicted severe or attenuated phenotype. - Results - Individuals with predicted attenuated forms of CTLN1 and ASA were overrepresented in the NBS group, while those with a predicted severe phenotype were underrepresented compared to individuals identified after the manifestation of symptoms (SX). Identification by NBS was associated with reduced severity of the initial HAE both in individuals with predicted severe and attenuated phenotypes, while it was not associated with lower frequency of (subsequent) HAEs. Similar results were obtained when including some patients diagnosed presymptomatically (i.e. prenatal testing, and high-risk family screening) in this analysis. - Conclusion - Since one of the major challenges of NBS outcome studies is the potential overrepresentation of individuals with predicted attenuated phenotypes in NBS cohorts, severity-adjusted evaluation of screened and unscreened individuals is important to avoid overestimation of the NBS effect. NBS enables the attenuation of the initial HAE but does not affect the frequency of subsequent metabolic decompensations in individuals with CTLN1 and ASA. Future long-term studies will need to evaluate the clinical impact of this finding, especially with regard to mortality, as well as cognitive outcome and quality of life of survivors.